PERAMALAN HASIL PRODUKSI PADI DI KABUPATEN LAMONGAN MENGGUNAKAN METODE DOUBLE EXPONENTIAL SMOOTHING - Asyiqqotus Saidah; Saiful Bahri (LPPM Universitas Bina Bangsa, 2024)
Food crops are an agricultural sub-sector that has a high contribution to the economy of Lamongan Regency. The increase in population growth rate affects the demand for food. In this study, the double exponential smoothing approach is used to forecast in order to avoid food shortages, especially rice. This method requires two parameters (α and β). This study uses data on rice production from the period 2009 to 2022. The results show that the best parameter values are α = 0,9 and ꞵ = 0,1 with a MAPE value of 11,72%. Based on the MAPE value, it is known that the forecasting model is good